Multiple choice qouestions in medical physiology with answers and reasoning - Chatterjee, Amar (Penerbit Universiti Teknologi Mara, 2011)
The aim of this book is to provide multiple choice questions on all aspects of medical physiology. It is hoped that the questions will be useful for medical, dental, nursing and health science students taking courses in medical physiology and also to the postgraduate students sitting for higher examinations.